Prospective Phase II Open-Label Randomized Controlled Trial to Compare Mandibular Preservation in Upfront Surgery With Neoadjuvant Chemotherapy Followed by Surgery in Operable Oral Cavity Cancer. Issue 3 (20th January 2022) - Chaukar, Devendra; Prabash, Kumar; Rane, Pawan; Patil, Vijay Maruti; Thiagarajan, Shivakumar; Ghosh-Laskar, Sarbani; Sharma, Shilpi; Pai, Prathamesh S.; Chaturvedi, Pankaj; Pantvaidya, Gouri; Deshmukh, Anuja; Nair, Deepa; et al.
Abstract : PURPOSE: The objective of this study was to explore the potential role and safety of neoadjuvant chemotherapy (NACT) in tumor shrinkage and resultant mandibular preservation in oral cancers compared with conventional surgical treatment. METHODS: This study was a single-center, randomized, phase II trial of treatment-naive histologically confirmed squamous cell carcinoma of the oral cavity with cT2-T4 and N0/N+, M0 (American Joint Committee on Cancer, seventh edition) stage, necessitating resection of the mandible for paramandibular disease in the absence of clinicoradiologic evidence of bone erosion. The patients were randomly assigned (1:1) to either upfront surgery (segmental resection) followed by adjuvant treatment (standard arm [SA]) or two cycles of NACT (docetaxel, cisplatin, and fluorouracil) at 3-week intervals (intervention arm [IA]), followed by surgery dictated by postchemotherapy disease extent. All patients in the IA received adjuvant chemoradiotherapy, and patients in the SA were treated as per final histopathology report. The primary end point was mandible preservation rate. The secondary end points were disease-free survival and treatment-related toxicity. RESULTS: Sixty-eight patients were enrolled over 3 years and randomly assigned to either SA (34 patients) or IA (34 patients). The median follow-up was 3.6 years (interquartile range, 0.95-7.05 years). Mandibular preservation was achieved in 16 of 34 patients (47% [95% CI, 31.49 to 63.24]) in the IA. The disease-free survival ( P = .715, hazard ratio 0.911 [95% CI, 0.516 to 1.607]) and overall survival ( P = .747, hazard ratio 0.899 [95% CI, 0.510 to 1.587]) were similar in both the arms. Complications were similar in both arms, but chemotherapy-induced toxicity was observed in the majority of patients (grade III: 14, 41.2%; grade IV: 11, 32.4%) in the IA. CONCLUSION: NACT plays a potential role in mandibular preservation in oral cancers with acceptable toxicities and no compromise in survival. However, this needs to be validated in a larger phase III randomized trial.